Verbal aspect in synoptic parallels : on the method and meaning of divergent tense-form usage in the synoptic passion narratives - Cirafesi, Wally V. (Linguistic Biblical Studies, 2013)
In Verbal Aspect in Synoptic Parallels Wally Cirafesi answers the question of why the Synoptic Gospels at times employ different tense-forms to communicate the same action. The problem has typically been explained from the perspective of redaction criticism and temporal Aktionsart approaches to the Greek verbesserte Cirafesi challenges these approaches by reframing the discussion in terms of recent advances in verbal aspect theory and discourse analysis. He convincingly demonstrates that such differences in tense-form usage have to do with how each Gospel writer wishes to construct their discourses according to various levels of linguistic prominence.